Expanding the genetic and clinical spectrum of osteogenesis imperfecta: identification of novel rare pathogenic variants in type I collagen-encoding genes - Paduano, Francesco; Fischetto, Rita; Moretti, Biagio; De Vito, Danila; Tatullo, Marco (Frontiers in Endocrinology, 2023)
Osteogenesis imperfecta (OI) is a clinically and genetically heterogeneous skeletal disorder. The majority of affected cases are attributed to autosomal dominant pathogenic variants (PVs) found in the COL1A1 and COL1A2 genes, which encode type I collagen. However, PVs in other genes involved in collagen posttranslational modification, processing, crosslinking, as well as osteoblast differentiation and bone mineralization have also been associated with OI. In this study, we present the results of next- generation sequencing (NGS) analysis using a custom panel of 11 genes known to be associated with OI. This clinical study enrolled a total of 10 patients, comprising 7 males and 3 females from 7 families, all from the Puglia Region in South Italy, providing a detailed overview of their age, gender, family history, OI type, and non-skeletal features. The genetic analysis revealed 5 PVs in the COL1A1 gene and 2 PVs in the COL1A2 gene. Importantly, three of these PVs have not been previously reported in the literature. These include two novel heterozygous frameshift PVs in COL1A1 (c.2890_2893del and c.3887del) and one novel heterozygous missense PV in COL1A2 (c.596G>T). The identification of these previously unreported PVs expands the variant spectrum of the COL1A1 and COL1A2 genes and may have implications for accurate diagnosis, genetic counselling, and potential therapeutic interventions in affected individuals and their families.